(untitled) (Biological Sciences - PJSIR, 2004)
Fresh Cassava processing effluent was obtained from a Cassava processing mill in Ekpoma, Edo State. One half of the fresh effluent was used to pollute top soil while the second half was aged for 7 days before use. The relative effects of the fresh and aged Cassava effluents on the physio - chemical properties of soil were determined. The effects of pollution varied with the soil/effluent contact period and the nature of the effluent. The result showed increase in the levels of pH, organic carbon, phosphorus, sodium, potassium; and decrease in calcium, magnesium and nitrogen in the soil after treat- ment with the effluents. There were no marked differences in the particle size distribution nature of the soil and the level of the exchangeable acidity after treatment with the effluents. The results showed that the disposal on the top soil of fresh and aged Cassava processing effluent could have diverse effects on the nutrient availability in the soil.